Peculiarities of separate forms of discretion according to the procedural law of Georgia - Shashiashvili, Giorgi (European Scientific Journal, ESJ, 2025)
In modern criminal proceedings, one of the key criteria for expressing the state’s democratic nature and high standard of rule of law is the legal and legitimate empowerment of participants in the justice process with "special authorities." This endowment is an indicator of the unique role they play within the process. However, granting such "special authorities" solely to certain participants can create an illusory appearance of privilege. In reality, these powers serve as tools for participants to perform positive roles in accordance with legally defined procedural procedures. This contributes to the effective and transparent administration of justice. The conducted research raises the question of whether it might be appropriate to refine and clearly define the framework within which process participants act, even within "special authorities," incorporating judicial oversight. The research conducted on the raised issue led us to relevant conclusions, which are fully reflected in the work. Through comparative and qualitative research methods, a rational analysis was conducted, suggesting possible legislative changes at the national level to expand and refine discretionary authority for the prosecutor and other participants in criminal proceedings.